From spectators to decision-makers: redefining student roles as co-designers of curriculum - Mustafa, Blerta; Gruda, Zinaide; Sarris, Julia (Frontiers in Education, 2025)
Partnering with students to co-construct curriculum is an initiative that is gaining considerable attention due to its potential to transform higher education. The aim of this longitudinal research was to explore the experiences of five MA students who were empowered to challenge the conventional pedagogy of their institution by engaging in a student-faculty partnership to reform the curriculum. As part of this novel shift, students investigated the department's pedagogical issues, seizing the chance to voice their concerns, recommend solutions, and contribute to the curriculum co-construction. This study employed a qualitative research design using semi-structured interviews obtained at two distinct timeframes, paired with instructors' reflective journals which were analyzed thematically. The findings indicate that the trajectory of such an initiative was affected by the entrenched norms of the institution such as fear of retaliation, and students' perceived lack of self-efficacy to influence change in the curriculum. Also, the unprecedented experience of questioning authority changed power dynamics, evoking a sense of discomfort for students. Nevertheless, the benefits of this partnership outweighed the obstacles. This study demonstrates that involvement in such initiatives cultivated a sense of agency and ownership, empowering students not only to make immediate adjustments to their study program but create a legacy for positive change in the academic experiences of successive generations. These results carry implications on the potential impact inclusive and collaborative pedagogies can have on breaking entrenched educational practices to progressively transform education.